Pediatrician's Guide to Discussing Research with Patients - Di Bartolo, Christina A.; Braun, Maureen K.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
With the proliferation of research studies posted online, media outlets scrambling to pick up stories, and individuals posting unverified information via social media, the landscape for parents trying to understand the latest science as it pertains to their children has never been more challenging to navigate. This book is intended to assist pediatricians when discussing research findings with parents. It provides an overview of research practices and terminology, clarifies misconceptions about studies and findings, and explains the limitations of research when applied to medical decision making. Through this framework, physicians can explain their reasoning behind specific clinical recommendations. In addition to examining the broad concepts comprising research literacy, this book reviews the current findings in topics that pediatricians report discussing most often with parents, such as vaccines, diet, medications, and sleep. Pediatrician$1 (Bs Guide to Discussing Research with Patients is a unique resource for pediatricians in encouraging the development of research literacy in their patients.s
1 Introduction -- 2 Funding and Bias -- 3 Study Design and Related Considerations -- 4 Significance: Statistical versus Clinical -- 5 Incorporating Research into Health Care Decisions -- 6 Vaccines -- 7 Diet -- 8 Food Allergies -- 9 Discipline Techniques -- 10 Medications -- 11 Sleep -- 12 Screen Time -- 13 School Refusal -- 14 Infectious Diseases. .
Keywords: Medicine; General practice (Medicine).; Pediatrics; Primary care (Medicine).; Medicine & Public Health; Pediatrics; General Practice / Family Medicine; Primary Care Medicine